2018
DOI: 10.1080/02786826.2018.1424315
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surfactants on growth of individual aqueous coarse mode aerosol particles

Abstract: Understanding the links between aerosol and cloud and radiative properties remains a large uncertainty in predicting Earth's changing energy budget. Surfactants are observed in ambient atmospheric aerosol particles, and their effect on cloud droplet growth is a mechanism that was, until recently, neglected in model calculations of particle activation and droplet growth. In this study, coarse mode aqueous aerosol particles were created containing the surfactant Igepal CA-630 and NaCl. The evaporation and conden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…18,20 Here, we calculate Köhler curves for dry particles composed of NAFA and NaCl of size 50-150 nm in 10 nm increments and Fig. 3, together with the corresponding ternary ts to eqn (5). Plots of measurement data and ternary ts for the remaining time steps t ¼ 0, 400, 600, and 800 s are presented in the ESI † as well as the residuals for all the ts.…”
Section: Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…18,20 Here, we calculate Köhler curves for dry particles composed of NAFA and NaCl of size 50-150 nm in 10 nm increments and Fig. 3, together with the corresponding ternary ts to eqn (5). Plots of measurement data and ternary ts for the remaining time steps t ¼ 0, 400, 600, and 800 s are presented in the ESI † as well as the residuals for all the ts.…”
Section: Modelingmentioning
confidence: 99%
“…Plots of measurement data and ternary ts for the remaining time steps t ¼ 0, 400, 600, and 800 s are presented in the ESI † as well as the residuals for all the ts. Ternary surface tension parameters resulting from the tting procedure described for eqn (5) are given in Table 1 for ts corresponding to all times steps. The surface tensions corresponding to time step t ¼ 0 s were previously presented by Kristensen et al, 21 who also presented raw time-evolving surface tension data for a single NAFA : NaCl mass mixing ratio of 80 : 20 at two single concentration points.…”
Section: Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other studies have also shown that ocean productivity and biomass abundance relate to the spatial and temporal variability in MBL particle and cloud droplet concentrations (McCoy et al, 2015;Meskhidze and Nenes, 2010;Vallina et al, 2006). While sulfate is more hygroscopic than organic aerosol mass, the latter still contributes to the particle size (which lowers the Kelvin effect) and may decrease the surface tension (Frossard et al, 2018;Ovadnevaite et al, 2017). Organics are likely to contribute to CCN concentrations considering organics often account for a significant fraction of marine Aitken-and accumulation-mode particle mass.…”
mentioning
confidence: 97%